Meningkatkan Kinerja UMKM Melalui Pemasaran Digital untuk Meningkatkan Produk Perusahaan - Yayan Listanto Alexander (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study aims to reveal several digital marketing strategies for baby clothes products and prove the efficiency of improving MSME performance through digital marketing. This research uses descriptive qualitative method. The power needed as a research knife is primary data that the author obtained by observing and interviewing parties related to this research. Secondary data was obtained from various books, journal articles, and other supporting literature. While the results of this study are: first, based on the opinion of MSME business owners who improve their performance through digital marketing by simply creating content that is interesting and easy for people to remember. Second, based on the opinions of MSME enthusiasts and customers, this "Mamawawa Baby Clothes Garment" can save costs and can be a strong competitor for those who don't use digital marketing. Third, based on the opinion of the general public, MSMEs really need increased work in terms of digital marketing to introduce product identity and MSME company identity in an era that uses the internet all the time.